Implementation of Islamic Religious Education Values in Early Childhood Moral and Religious Development - Nurjamilah, Umi (Journal of Childhood Development, 2024)
This research aims to analyze the implementation of Islamic religious education values ​​in the moral and religious development of early childhood. The method used in this research is a qualitative approach, with data collection through observation, interviews and document analysis in Telaga Sunnah Kindergarten, Tulangbawang. The research results show that the application of Islamic religious education values, such as through example, habituation, honesty, responsibility and compassion, significantly contributes to the formation of children's character and morals. Interactive learning methods, including games, stories and group activities, facilitate children's understanding of these values. Apart from that, support from parents and the surrounding environment has proven to be very important in strengthening the implementation of the values ​​of Islamic Religious Education. This research concludes that Islamic religious education at an early age plays an important role in building children's morals and social responsibility, and recommends the need to increase cooperation between educators, parents and the community in supporting children's moral and religious development.